2015
DOI: 10.1088/0029-5515/55/4/043020
|View full text |Cite
|
Sign up to set email alerts
|

An active feedback recovery technique from disruption events induced bym= 2,n= 1 tearing modes in ohmically heated tokamak plasmas

Abstract: We present experimental results of magnetic feedback control on the m=2, n=1 tearing mode in RFX-mod operated as a circular ohmically heated tokamak. The feedback suppression of the non-resonant m=2, n=1 Resistive Wall Mode (RWM) in q(a)<2 plasmas is a well-established result of RFX-mod. The control of the tearing counterpart, which develops in q(a)>2 equilibrium, is instead a more difficult issue. In fact, the disruption induced by a growing amplitude m=2, n=1 tearing mode can be prevented by feedback only wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…The experiments have demonstrated that magnetic feedback realized by active saddle coils placed outside the 100ms time-constant copper shell is able to push a wall locked m=2, n=1 mode into slow rotation with frequency of the order of several tens of Hertz. Such result has been shown to remain valid when replicated in DIII-D diverted, D-shaped, high-β plasmas, controlled by coils placed inside the 5ms time-constant vacuum vessel [58,59]. Simulations with the RFXlocking electromagnetic code indicate the improved efficiency of the feedback control with respect to the feedforward one [58].…”
Section: Avoidance Of M=2 N=1 Tearing Mode Walllocking With Magneticmentioning
confidence: 88%
“…The experiments have demonstrated that magnetic feedback realized by active saddle coils placed outside the 100ms time-constant copper shell is able to push a wall locked m=2, n=1 mode into slow rotation with frequency of the order of several tens of Hertz. Such result has been shown to remain valid when replicated in DIII-D diverted, D-shaped, high-β plasmas, controlled by coils placed inside the 5ms time-constant vacuum vessel [58,59]. Simulations with the RFXlocking electromagnetic code indicate the improved efficiency of the feedback control with respect to the feedforward one [58].…”
Section: Avoidance Of M=2 N=1 Tearing Mode Walllocking With Magneticmentioning
confidence: 88%
“…The flow oscillates at the same frequency as the MHD modes, i.e. the 2/1 RWM and the internal 1/1 kink mode, which are maintained into rotation by the magnetic feedback control system [5,23]. By correlating flow measurements with radial magnetic field data, the presence of helical flow and m = 1, n = 1 convective cells has been inferred.…”
Section: Introductionmentioning
confidence: 95%
“…The novelty of the experiments reported in this paper is that, in the presence of rotating 3D magnetic fields, oscillations have been observed in the plasma flow, measured by the Doppler shift of spectral lines from several ion species. The flow oscillates at the same frequency of the MHD modes, which are maintened into rotation by the magnetic feedback [8,11]. By correlating flow measurements with radial magnetic field data, m = 1, n = 1 (with m and n poloidal and toroidal mode numbers, respectively) convective cells have been inferred in the flow pattern, which are a signature of helical flow.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The maximum plasma current achieved in tokamak operations is I p = 0.15 4 MA, with a maximum toroidal magnetic field B φ = 0.55 T, corresponding to an edge safety factor q a = 1.7. This low-q operations are possible only by means of a feedback control on the (m = 2, n = −1) mode, that resonates close to the wall and would otherwise grow too large and disrupt the discharge [33]. In the following sections we present the results obtained by analyzing and reconstructing the topology in a typical tokamak discharge of RFX-mod, with q a 2.1 and where a resonant (2, -1) perturbation with a rotation frequency of 10 Hz is applied through the feedback control system.…”
Section: Experimental Setup and Diagnosticsmentioning
confidence: 99%